THE STUDENTS’ PERCEPTIONS OF AUTHENTIC TEXTS-BASED TRANSLATION - Rusiana . (IAIN MADURA, 2017)
Translation requires lots of practice. As it is generally known, authentic texts provide fruitful experience for students to translate either Indonesian-English or vice versa. Authentic texts give many real uses of language in varied meaningful contexts The texts used were advertisement, abstract, local stories, tourist attraction, community service and project for money. This research is aimed at investigating whether the use of authentic texts benefits the students and describing the students’ perceptions toward the use of authentic texts in Translation class. It is a qualitative research. Questionnaires were used to obtain the students’ perceptions on the use of authentic texts in translation. The findings show that authentic texts-based translation benefits students in experiencing better translation. Advertisement was considered to be the most relevant text. On the contrary, they find it difficult to cope with authentic texts particularly dealing with words/terms/vocabulary, meanings, culture, and grammar. The recommendations are that the students have to be exposed to many authentic texts of varied topics in both English and Indonesian in order that they understand both the SL and TL well. For further researchers, it would be possible to research on the influence of authentic texts based translation on the students’ translation skill.